Quota-Based Compensation Plans for Multiterritory Heterogeneous Salesforces - Raju, Jagmohan S.; Srinivasan, V. (Management Science, 1996)
We compare quota-based salesforce compensation plans with the BLSS plan, i.e., the optimal curvilinear agency-theory-based compensation plans proposed in Basu, Lal, Srinivasan and Staelin (Basu, A. K., R. Lal, V. Srinivasan, R. Staelin. 1985. Salesforce compensation plans: An agency theoretic perspective. Marketing Sci. 4(Fall) 267–291.). A quota plan pays a fixed salary which is supplemented by commission income that is a prespecified fraction of the dollar sales that exceed the quota. For a salesforce comprised of multiple salespersons/territories, we consider a basic quota plan where the commission rate and salary remain the same across salespersons; however, quotas vary across salespersons/territories. Compared to the BLSS plan that is individually tailored to each salesperson/territory, the basic quota plan's total nonoptimality in profit has two components: (i) a shapeinduced nonoptimality arising from the fact that the quota-based plan does not have the same optimal shape as the curvilinear BLSS plan, and (ii) a heterogeneity-induced nonoptimality arising from the fact that the salary and commission rate in the basic quota plan are constrained to be the same across the salesforce. Our numerical experiments indicate that the total nonoptimality is merely about 1% for the parametric scenarios studied. The basic quota plan is simpler to implement than the BLSS plan. Furthermore, changes in business conditions in a territory, or the transfer of a salesperson from one territory to another, can be accommodated by changing only the quota, without having to change the salary and the commission rate structure. Such advantages, together with our result that the nonoptimality is slight, suggest that quota-based plans offer considerable potential as a salesforce compensation scheme.